Developing a novel technology for slurry management by project-based learning - Moure Abelenda, Alejandro; Roberts, Jenny (Frontiers in Sustainable Food Systems, 2024)
Farming is responsible for 30% of global anthropogenic emissions. A novel technology, aligning with current regulations of covering slurry stores, has been developed for processing anaerobic digestate liquor, which is obtained from the screw press stage. Instead of using hazardous chemicals, such as sulfuric acid, to capture ammonia and greenhouse gases, the artifact contains calcium chloride as deliquescent salt. Preliminary simulations in Aspen Plus® v12 showed that the absorption of NH3 and carbon dioxide during the solid–liquid separation was feasible and the resulting clean brine could be used as chemical amendment of untreated slurry. The characterization of the performance of the artifact was organized following a project-based learning active teaching method, for a group of 3 students (17-year-olds) of secondary education, as part of the In2ScienceUK program. The collection of empirical data allowed the contents of the curriculum to be contextualized, enhancing environmental awareness of participants. A titrimetric method was employed to determine the content of NH3 and CO2 in the brine, and the granulation of the dewatered liquor with the fibers of anaerobic digestate was investigated by determining the compression strength required to break the pellets. The operation capacity of the prototype was found to be 250 m3 of liquor per year, at a cost of £1/m3. The use of the filtered brine as chemical amendment also represented an additional 5.60 grams of ammoniacal nitrogen and 0.96 grams of inorganic carbon per cubic meter of unprocessed slurry. The concentrated liquor was a good binding agent that provided the pellets with a compressive strength of 207.00 ± 26.36 N, which was above the threshold value for commercialization purposes (50 N). The advances in the development of the prototype enhanced the suitability of the technology for industrial scale applications but hindered the adoption of subsequent editions of this pedagogic tool.